HAKIKAT MONOTEISME ISLAM (KAJIAN ATAS KONSEP TAUHID “LAA ILAAHA ILLALLAH”) - Roni Ismail (UIN Sunan Kalijaga Yogyakarta, 2014)
According to Islam, all humans are bor n in a state of fitrah or an innate inclination of tawhid (Oneness). In a further development, some people deviated from their fithrah, some remains in their desposition depending on the milieu affecting them, especially their parent. The concept of divinity or theology taught by Islam are monotheistic, and it is in line with the pure human nature. The monotheistic theology of Muslims, known as “tauhid” is formulated in the in the confession of faith saying “laa ilaha illallah”, meaning “there is no god, but Allah.” This paper describes the concept of monotheism in Islam based on the meaning of “La ilaha Illallah” and their implications in ever yday life.